Sun Avoidance Measures and Factors Associated with Low Outdoor Time among Healthcare Undergraduate Students, University of Jaffna - Paramanathan, T.; Arasaratnam, V.; Sivayokan, B. (Faculty of Medicine University of Colombo, 2023)
Many people in Asian countries have Vitamin D deficiency, despite getting sunlight throughout the year. This study was carried out to evaluate the sun avoidance measures and factors associated with low outdoor time of healthcare undergraduates in Sri Lanka.
Keywords: Sun avoidance; Outdoor time; Vitamin D; Undergraduate healthcare students